210k views
0 votes
Follow these steps using the algebra tiles to solve the equation -5x + (-2) = -2x + 4

User Marilene
by
5.8k points

2 Answers

5 votes

Answer:

x=-2

Explanation:

User Aman Chhabra
by
4.8k points
6 votes

Answer:

x=-2

Explanation:

−5x−2+2x=−2x+4+2x

−3x−2=4

Step 2: Add 2 to both sides.

−3x−2+2=4+2

−3x=6

Step 3: Divide both sides by -3.

−3x

−3

=

6

−3

x=−2

User Mouse On Mars
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.